TRANSFORMASI LITERASI DIGITAL SISWA MELALUI PENGEMBANGAN APLIKASI ANDROID BERBASIS MODUL INTERAKTIF DAN VIDEO EDUKATIF DI MTS AL HUDA BANDUNG BARU - Muhammad Andriansyah; Linda Monika; Siti Mukodimah (YHMM PUBLISHING, 2025)
The rapid advancement of digital technology has increased the importance of digital literacy as a fundamental competency for students. However, many secondary school students continue to experience difficulties in understanding and applying essential digital literacy concepts, particularly in the areas of digital ethics, cybersecurity, information evaluation, and responsible technology use. Preliminary observations at MTs Al Huda Bandung Baru revealed that smartphones were predominantly utilized for entertainment purposes rather than educational activities, indicating the need for innovative learning media that can support digital literacy development. This study aimed to develop and evaluate EduTech, an Android-based learning application integrating interactive modules, educational videos, and assessment quizzes to enhance students’ digital literacy competencies. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The application was developed using the Flutter framework with a local SQLite database, enabling full offline functionality to accommodate diverse learning environments. Functional feasibility was assessed through Black Box Testing, while effectiveness was evaluated using a One-Group Pre-test Post-test design involving 30 eighth-grade students. Data were analyzed using descriptive statistics to measure changes in students’ digital literacy understanding before and after the intervention. The findings demonstrated that all functional testing scenarios achieved a 100% validity rate, confirming the reliability and usability of the application. Furthermore, students’ mean scores increased substantially from 52.40 in the pre-test to 81.60 in the post-test, indicating a significant improvement in digital literacy comprehension. The results suggest that the integration of interactive learning materials, multimedia content, and self-assessment features effectively supports students’ engagement and learning outcomes. This study concludes that EduTech is a feasible and effective mobile learning solution for strengthening digital literacy education and may serve as a scalable model for technology-enhanced learning in secondary education settings.